Are operations backed by best practices in American problem-solving courts? - Smith, Lindsay R.; Faragó, Fanni; Blue, Thomas; Witte, James C.; Gordon, Michael S.; Taxman, Faye S. (Journal of Substance Use, 2025)
Background: Problem-solving courts (PSCs) are specialized courts offering evidence-based interventions for rehabilitating and diverting individuals from carceral institutions. PSCs allow participants to address problems influencing their behavior, such as mental health and/or substance use disorders, while remaining in the community under court supervision. PSCs are designed to serve as linkage sites to support services and research supports PSCs' efficacy in doing so. Objective: Less is known about how PSC operations align with national best practices specified by All Rise (professional association of PSCs) in serving court participants. Methods: This study explores whether American PSCs adopt All Rise's 10 best practice principles based on surveys from a larger study of PSC operations reported by local (n = 849) and state (n = 42) PSC coordinators. Results: Of the All Rise principles captured in our study, only 4% of courts adopted eight EBPs whereas 56% of the courts adopted four to six EBPs. PSCs using EBPs employed diversified staff positions, collaborated with multiple treatment providers, participated in treatment trainings, offered peer navigators, used validated screening tools, used varied treatment modals, and had eligibility criteria for participants to enter PSC programs. Conclusions: PSCs' operations were generally backed by some of All Rise's best practices.